2021
DOI: 10.1002/joa3.12578
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 induced bradyarrhythmia and relative bradycardia: An overview

Abstract: Novel coronavirus 2019 (COVID‐19) has been the focus of the medical community since its emergence in December 2019 and has already infected more than 100 million patients globally. Primarily described to cause a respiratory illness, COVID‐19 has been found to affect almost every organ system. Bradycardia is a newly recognized ramification of COVID‐19 that still has unknown prognostic value. Studies have shown an increase in the incidence of arrhythmias, cardiomyopathies, myocarditis, acute coronary syndromes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
1
20
0
8
Order By: Relevance
“…Bradyarrhythmias were more likely to be observed in centers in Asia, while atrial fibrillation was less common [44]. There has been some recognition that elderly COVID-19 patients may have an impaired heart rate response to fever [45]. Relative bradycardia, defined as heart rate less than 90 bpm and concomitant fever, was observed in 40 out of 110 retrospectively reviewed patients in Switzerland.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…Bradyarrhythmias were more likely to be observed in centers in Asia, while atrial fibrillation was less common [44]. There has been some recognition that elderly COVID-19 patients may have an impaired heart rate response to fever [45]. Relative bradycardia, defined as heart rate less than 90 bpm and concomitant fever, was observed in 40 out of 110 retrospectively reviewed patients in Switzerland.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…Cardiac complications are known to be associated with the COVID-19 disease caused by the novel Severe Acute Respiratory Syndrome—Coronavirus 2 (SARS-CoV-2) ( Cizgici et al, 2020 ; Huang et al, 2020 ; Kochi et al, 2020 ; Long et al, 2020 ; Shi et al, 2020 ; Siripanthong et al, 2020 ; Wang et al, 2020 ; Coromilas et al, 2021 ). An unusual feature that is sometimes seen in patients diagnosed with COVID-19 is the appearance of bradycardia, i.e., slow heart rate, or heart rate not increasing as expected with body temperature ( Ikeuchi et al, 2020 ; Capoferri et al, 2021 ; Douedi et al, 2021 ; Oliva et al, 2021 ). Amaratunga et al (2020) found bradycardia in a study of 4 patients with confirmed COVID-19, with minimum pulse rates in the range 42–49 beats per minute.…”
Section: Introductionmentioning
confidence: 96%
“…One proposed mechanism is that the cytokine storm produced by severe SARS-CoV-2 infection directly affects the sinoatrial node leading to bradycardia [20]. Previous studies have also reported that bradycardia in COVID-19 patients is not associated with hypoxia, myocardial ischemia, or medications that induce bradycardia [17,18].…”
Section: Discussionmentioning
confidence: 99%